The spectrum of a class of almost periodic operators - Norbert Riedel (International Journal of Mathematics and Mathematical Sciences)
For almost Mathieu operators, it is shown that the occurrence of Cantor spectrum and the existence, for every point in the spectrum and suitable phase parameters, of at least one localized eigenfunction which decays exponentially are inconsistent properties.